Polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) prediction model based on limited peat samples using an evolved artificial neural network - Wang Shir Li, Sumayyah Dzulkifly (Tanjung Malim, 2024)
Polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) prediction model based on limited peat samples using an evolved artificial neural network by Wang Shir Li, Sumayyah Dzulkifly